2014
DOI: 10.2298/mpns14s1061s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nasal septum deformity degree on subjective nasal breathing assessment

Abstract: Introduction. The aim of this paper is to determine the influence of nasal septum deformity degree on the subjective nasal breathing assessment as well as the existence of correlation between one side of the nose with nasal septum deformity and the subjective feeling of difficulty in breathing on that side in the subjects with different degrees of nasal septum deviation. Material and Methods. The research included 90 randomly chosen patients, who claimed to have nasal breathing difficulties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…1 ). 8 , 13 Briefly, the angle was measured between two lines of reference. The first line running from the nasal septum insertion in the maxillary crest and the junction point of the perpendicular and the cribriform plate corresponded to the midline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). 8 , 13 Briefly, the angle was measured between two lines of reference. The first line running from the nasal septum insertion in the maxillary crest and the junction point of the perpendicular and the cribriform plate corresponded to the midline.…”
Section: Methodsmentioning
confidence: 99%
“…However, the few studies that correlated CT images and subjective nasal obstruction symptoms reported conflicting results about which morphological characteristics of the NSD, if any, should be recommended as an indicator of the symptom severity. 8 , 9 , 10 Besides contradictory results, CT was used only for NSD angle and cross-sectional area measurement in the different parts of the nasal cavity. An advantage of the CT to show the detailed morphology of the deviated septum was not fully utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Classification according to the maximal NSD angle (C5) grades deviation into mild, moderate, and severe. 12,17 The maximal NSD angle measurement was carried out like in the previous studies (an angle between the line that connects the crista galli and the nasal crest and the second line that joins the crista galli with the maximal deviation point). 10,12,18 For the S-shaped NSDs, a greater angle was taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…There are various classification systems of NSD in the literature, but none is generally accepted. Recent CT studies mainly considered the angle of deviation, [10][11][12] whereas other anatomical parameters of NSD such as single or double curve, presence of the spur, and which septal structure is affected by deviation (bone or cartilage) were not examined at all in the context of the nasal obstruction severity. Currently, there is no CT study that comprehensively evaluated different morphological modalities of NSD and connected them with the subjective perception of nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation